1990
DOI: 10.1093/jn/120.3.233
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, Transport and Distribution of Vitamin E

Abstract: Vitamin E is the term used for eight naturally occurring fat-soluble nutrients called tocopherols. alpha-Tocopherol is essential, has the highest biological activity and predominates in many species. In humans vitamin E is the most important lipid soluble antioxidant and deficiency may cause neurological dysfunction, myopathies and diminished erythrocyte life span. alpha-Tocopherol is absorbed via the lymphatic pathway and transported in association with chylomicrons. In plasma, alpha-tocopherol is found in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
143
0
14

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(161 citation statements)
references
References 114 publications
4
143
0
14
Order By: Relevance
“…Vitamin E is a potent scavenger of peroxyl radicals within the membranes [45,46]. The polar ␣-tocopheryl esters, namely vitamin E succinate, have proven valuable tools for supplementing ␣-tocopherol to isolated cells, increasing the resistance of cells to oxidative damage [47].…”
Section: Formation Of Ros and Protection By Vitamin E And Idebenonementioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin E is a potent scavenger of peroxyl radicals within the membranes [45,46]. The polar ␣-tocopheryl esters, namely vitamin E succinate, have proven valuable tools for supplementing ␣-tocopherol to isolated cells, increasing the resistance of cells to oxidative damage [47].…”
Section: Formation Of Ros and Protection By Vitamin E And Idebenonementioning
confidence: 99%
“…Vitamin E distributes to cellular membranes and is located in the mitochondrial fractions and in the endoplasmic reticulum [45]. Ray and Fariss [53] proposed the accumulation of vitamin E succinate at the level of mitochondria, where it could exert its antioxidant activity.…”
Section: Formation Of Ros and Protection By Vitamin E And Idebenonementioning
confidence: 99%
“…These enzymes are responsible for removing superoxide radicals, H 2 O 2 and organic hydroperoxides. Additional antioxidant enzymes such as thioredoxin, glutaredoxin, and peroxiredoxin reductase also contribute to cellular protection against oxidation [13,18]. An acute exercise or longer term exercise result in increased activities of superoxide dismutase, catalase or glutathione peroxidase in animal and human muscles [6 Superoxide dismutase must work with enzymes that remove H 2 O 2, that is with catalase.…”
Section: A) Primary Antioxidant Enzymesmentioning
confidence: 99%
“…Supplementation with tocotrienol-rich fractions (TRF) from palm oil, a potent antioxidant from the natural Vitamin E family, may help in the prevention or treatment of several diseases [45]. Studies have shown vitamin E supplementation as an efficient means of reducing exercise-induced muscle damage due to free radical formation [18].…”
Section: Vitamin E-tocopherolmentioning
confidence: 99%
See 1 more Smart Citation